Design of Prototype Payment Application System With Near Field Communication (NFC) Technology based on Android - Huda Ubaya (Computer Engineering and Applications Journal, 2012)
Since the late 1990s, people have enjoyed a comfortable lifestyle. Mobile devices supported by the development of wireless networks have spread throughout the world. People can get information, order tickets, download songs and perform commercial transactions, called mobile commerce. Mobile commerce applications become the most popular application for mobile device users who want to do business and financial transactions easily and securely, anytime and anywhere they are. Today the use of physical cash is experiencing a decline in popularity in the business world, because it is being replaced by non-physical payments are often called electronic money (e-money). An important technology behind mobile payments is called Near Field Communication (NFC). As an indication that the NFC has tremendous business potential, leading companies like Nokia, Microsoft, Visa Inc., and MasterCard Worldwide and NXP Semiconductors, is actively engaged on them. Payment processing integrated with NFC technology based mobile operating system that is a trend today is Android that support NFC technology is version 2.3.3 Gingerbread. The prototype application is designed to pay for 2 on the user side of the user as consumer and the merchant side as a trader or seller by using the handset that already have NFC technology is Google Samsung Nexus S. Pay an application prototype also implements the concept of security in e-commerce transactions by using the protocol-to-Tag Tag so that the user needs for security and comfort during the financial transaction are met.